Prevalence and risk factors of Chlamydia trachomatis genital infection among military personnel of the Armed Forces of Serbia: a cross-sectional study - Jadranin, Željko P; Ristanović, Elizabeta; Atanasievska, Sonja; Dedić, Gordana; Šipetić - Grujičić, Sandra; Bokonjić, Dubravko; Grillo, Michael; Mladenović, Jovan; Bančević, Vladimir; Kosević, Branimir; Šuljagić, Vesna (Vojnosanitetski pregled, 2021)
Abstract Background/Aim. Chlamydia trachomatis infection (CTI) is an increasing public health problem worldwide and is the most frequent sexually transmitted infection. Studies conducted in many armed forces worldwide showed that CTI is common within military population and generate significant healthcare costs. The aim of this study was to estimate the prevalence of CTI among members of the Serbian Armed Forces (SAF) and to determine risk factors for this infection. Methods. The study was designed as a cross-sectional survey and consisted of completing a questionnaire and chlamydial testing. The questionnaire was divided into two question groups: one was about demographic/service related characteristics and the other was about behavioral patterns/habits. Chlamydia trachomatis real time polymerase chain reaction (Real-TM PCR) was used for detection of pathogen genome specific sequence in the male urethral swabs and in the female endocervical swabs. All data collected were used to compare military personnel with and without CTI. Risk factors independently associated with CTI were identified by the stepwise multivariate logistic regression analysis (MLRA) of variables selected by the univariate logistic regression analysis (ULRA), with a limit for entering and removing variables from the model at 0.05. Results. The overall prevalence of CTI was 55 of 356 respondents (15.4%; 95% CI 0.5–2.7%). The ULRA identified that CTI was significantly associated with several characteristics: number of sexual partners during previous year (p = 0.008), knowledge about symptoms of CTI (p = 0.035), tattooing (p = 0.035) and married or in stable relationship (p = 0.022). The MLRA revealed that number of different sexual partners during last year was independent risk factor of CTI (p = 0.026; OR : 0.344; 95% CI: 0.13–0.88). Conclusion. CTI is significant problem in male and female military personnel in the SAF. The number of different sexual partners during previous year was independently associated with CTI. These finding indicates that screening for CTI should be undertaken in the SAF, to reduce rates of CTI in the SAF and to prevent morbidity due to this infection.